1982
DOI: 10.1002/hlca.19820650121
|View full text |Cite
|
Sign up to set email alerts
|

[2 + 2]‐Cycloadditions to Strained Bridgehead Olefins. I. 1, 1‐Dichloro‐2,2‐difluoroethene

Abstract: The strained bridgehead olefins bicyclo [3.3.l]non-l-ene (I), bicyclo [4.2. llnon-1 (8)-ene (2), and bicyclo [4.2.l]non-l-ene (3) react rapidly with I, 1-dichloro-2,2difluoroethene (5) to yield mixtures of regioisomeric dichlorodifluorocyclobutanes 8/9, 10/11 and 12/13, respectively. On the contrary, the reaction of 5 with the model compound (E)-1 -methylcyclooctene (4) is completely regioselective. The structure of the cycloadducts has been elucidated mainly by 19F-NMR. and 13C-NMR. spectroscopy.Introduction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Given the very low rotational and radical combination barriers, the diradical intermediates reside on a relatively flat energy surface and are susceptible to nonstatistical dynamic effects. 37−41 We further examined the reactions of 12 and 14 with 1,1dichloro-2,2-difluoroethene, previously reported by Becker and Hohermuth 21 (Figure 3b,c). As expected by an increased p character at the F-substituted carbon of 1,1-dichloro-2,2difluoroethene, a σ-bond first forms between the CF 2 fragment and either C1 (via TS1) or C2 (via TS1′) of the bicyclic compound.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Given the very low rotational and radical combination barriers, the diradical intermediates reside on a relatively flat energy surface and are susceptible to nonstatistical dynamic effects. 37−41 We further examined the reactions of 12 and 14 with 1,1dichloro-2,2-difluoroethene, previously reported by Becker and Hohermuth 21 (Figure 3b,c). As expected by an increased p character at the F-substituted carbon of 1,1-dichloro-2,2difluoroethene, a σ-bond first forms between the CF 2 fragment and either C1 (via TS1) or C2 (via TS1′) of the bicyclic compound.…”
mentioning
confidence: 95%
“…19,20 By comparing the reaction of 2norbornene (16) to that of bicyclo[4.2.1]non-1-ene (12) and bicyclo [3.3.1]non-1-ene ( 14), Becker and Hohermuth showed that the strained double bonds of 12 and 14 yielded faster stepwise [2 + 2] cycloadditions with 1,1-dichloro-2,2difluoroethene and at milder conditions. 21 12 and 14 also gave facile concerted [2 + 2] cycloaddition reactions with a ketene. 22 The twisted double bonds of trans-cycloalkenes (n = 7−10, n is the number of ring atoms) exhibit higher reactivity compared to their unstrained cis-analogues.…”
mentioning
confidence: 99%
See 3 more Smart Citations